Consequences For Nigeria's Democracy and the Cost Of Governance. - Ajiteru, S.A.R; Sulaiman, T.H; Abalaka, J.N (Green Social: International Journal of Law and Civil Affairs, 2025)
President Goodluck Jonathan established the Presidential Committee on Rationalization and Restructuring of Federal Government Parastatals, Commissions, and Agencies in August 2011 in an effort to reduce the growing cost of government. The committee, led by Stephen Orosanye, the former Head of the Civil Service of the Federation, produced a report that included various recommendations, some of which have caused uncertainty and anxiety among government workers. The committee reviewed existing legislation and noted in the report that "Nigeria's average cost of governance is considered to be among the highest in the world." All branches of government must work diligently to reduce operating costs if the cost of governance is to be lowered. The report suggested reducing the 263 agencies to 161, with additional recommendations: 38 agencies should be abolished, 52 merged, and 14 transferred back to departments within relevant ministries. It is estimated that around 30,000 people work in these agencies and parastatals, though the exact figures vary. However, it is still unclear how the National Assembly will accept these proposals, given that most of these institutions were established by legislation. Orosanye’s Report has attracted more criticism than support, based on public opinion reflected in the media. The aim of this research is to investigate the impact of high governance costs on Nigeria's socioeconomic sectors.